Responses of microbial structures, functions, metabolic pathways and community interactions to different C/N ratios in aerobic nitrification. (September 2020) - Sun, Hongwei; Shi, Wenyan; Cai, Chenjian; Ge, Shijian; Ma, Bin; Li, Xiaoqiang; Ding, Jing
Graphical abstract: Highlights: The highest microbial diversity was discovered at C/N ratio of 0. Low C/N ratios enhanced the Nitrosomonas, Nitrospira, amo and nirK . Metabolisms of amino acid, carbohydrate and energy were predominant. TN removal and AOR were positively linked to hcp and amo, respectively. Abstract: The responses of microbial structures, functional profiles and metabolic pathways during nitrification to four C/N ratios (0, 5, 10 and 15) were investigated in four parallel SBRs denoted as S0, S5, S10, S15 . Results indicated that microbial diversities were affected by C/N ratios, while the same dominant taxa were observed, mainly including Proteobacteria, Betaproteobacteria, Rhodocyclales, Rhodocyclaceae, Zoogloea . The unique biomarkers were identified in each sludge sample through LEfSe analysis. Functional genera/enzymes responsible for removing organics and nitrogen coexisted in four SBRs at different abundances, except for that ammonia oxidizing bacteria (AOB) Nitrosomonas (0.33%–0.66%) and ammonia monooxygenase ( amo ) (9.4 × 10 −7 –2.8 × 10 −6 ) were only detected in S0 . Moreover, PICRUSt analysis indicated similar overall patterns of metabolic pathways in four sludge samples. The network analysis revealed that total nitrogen removal positively correlated with hcp (Spearman's ρ of 0.853), and ammonia oxidizing rate was associated with amo (Spearman's ρ of 0.096).